Wulgaryzacja przekazu jako wyróżnik języka w komunikacji na forach internetowych - Staszewska, Justyna (Acta Universitatis Lodziensis. Folia Linguistica, 2010)
The article characterizes the phenomenon of vulgarization in Internet forums. The author gives examples and descriptions of different ways of using verbal aggression. Vulgarisms are frequently designed for: emphasize someone’s emotions, authenticate someone’s statements, autopresentation, elicitation other people participating in an Internet forum. It is symptomatic, that vulgarisms become more and more popular in language of online discussions.